The role of gut microbiota in modulating immune responses: a systematic review on implications for autoimmune diseases - Saran, Aditya B.; Saran, Aditi B. (International Journal of Research in Medical Sciences, 2025)
The gut microbiota plays a crucial role in immune regulation, influencing innate and adaptive immunity. Dysbiosis an imbalance in microbial composition has been linked to autoimmune diseases such as rheumatoid arthritis (RA), type 1 diabetes (T1D), multiple sclerosis (MS), inflammatory bowel disease (IBD) and systemic lupus erythematosus (SLE). This review analyses sixteen studies, highlighting common dysbiosis patterns, including decreased short-chain fatty acid (SCFA)-producing bacteria (Faecalibacterium prausnitzii, Bifidobacterium) and increased pro-inflammatory bacteria (Prevotella copri, Akkermansia muciniphila). These shifts contribute to autoimmunity via molecular mimicry, increased gut permeability and immune dysregulation. Microbiota-targeted therapies such as probiotics, prebiotics, dietary interventions and fecal microbiota transplantation (FMT) show promise in restoring microbial balance and modulating immune responses. Probiotics (Lactobacillus reuteri) reduce inflammation in RA and MS, while FMT partially restores microbial diversity in IBD and MS. Despite progress, causality remains unclear, necessitating longitudinal studies and personalized microbiome-based interventions. Understanding the gut microbiota-autoimmunity relationship could pave the way for microbiome-driven immunotherapies.